Assessing the Relationship between Entrepreneurship and Economic Development in the MENA Region: An Empirical Investigation. Issue 5 (2022) - Benghalem, Abdelhadi; Maliki, Samir; Kertous, Mourad; Hilmi, Nathalie
No abstract available